Get great marks for your essays - Germov, John. (St Leonards, N.S.W. : Allen and Unwin, 2000)
Being an academic detective; The rules of the essay writing game; The art of analysis...
Keywords: English language; Rhetoric; Report writing; Report writing; English language -- Rhetoric